Pengaturan Juru Bahasa Isyarat dalam Pembuatan Akta Otentik oleh Notaris bagi Penghadap Tunarungu - Pradnyadewi, Ida Ayu Putu Kurnia; Jayantiari, I Gusti Agung Mas Rwa (Law and Human Rights Research and Development Agency, 2023)
The objective of this paper is to analyze the arrangement for sign language interpreters in making authentic deeds by a Notary for deaf appearers in Indonesia and to analyze the relevant arrangements regarding this issue in terms of the provision of sign language interpreters by a Notary for deaf appearers in the future. The benefit of this writing is to provide a juridical understanding regarding the arrangements for providing sign language interpreters in making authentic deeds by a Notary for deaf appearers in Indonesia as well as providing scientific contributions in the dimension of the Notary Act. The void of norms underlying writing uses a type of normative legal research through statutory and comparative approaches which are analyzed using descriptive, comparative, argumentative, and prescriptive techniques. The results of the study show that the authority of a Notary to make authentic deeds is contained in Article 15 paragraph (1) of the Amendment to the Act on the Position of Notary. This arrangement is intended for appearers with non-disabled conditions only because it contains a “sufficiently clear” clause. Based on a comparative study of the Amendment to the Act on the Position of Notary and the Japanese Notary Act, the Amendment to the Act on the Position of Notary has not regulated the provision of sign language interpreters for deaf appearers, while the Japanese Notary Act has regulated sign language interpreters. Resolving the urgency of this problem by formulating arrangements for sign language interpreters in the Amendment to the Act on the Position of Notary by adopting the provisions contained in the Japanese Notary Act.